Item Analysis Training Problems with Software to Improve Teacher’s Competencies in Blitar - Yuniawatika; Lilik Bintartik; Harti Kartini; Sri Estu Winahyu; Ibrahim Sani Ali Manggala (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
One of the demands of a professional teacher is being able to make quality questions. Item analysis is one way to obtain quality questions. Therefore, in this community service, the PKM team conducted an item analysis training held at Campus 3 of Malang State University in Blitar City, which was attended by 19 teacher participants from three sub-district representatives in Blitar City. The purpose of this dedication is to: (1) increase the awareness of teachers the importance of analyzing items, (2) provide insight about compiling good instruments and analyze items so that they get quality instruments, (3) assist to teachers in analyzing items using ITEMAN, Anates, and Excel. The method of carrying out this dedication activity is carried out with lectures, demonstrations, and practices, assignments, discussions, and presentations. The training was held for four days and was attended by all participants in a disciplined and orderly manner. PKM results show that all participants were able to (1) compile a good test instrument, (2) understand the importance of analyzing items, (3) analyze items using software using ITEMAN, Anates, and Excel.